Conjoining imperatives and declaratives - Starr, William B. (Proceedings of Sinn und Bedeutung, 2019)
This paper investigates conjoined imperatives and declaratives (IaDs). It argues that some IaDs are best explained in terms of true conjunction and anaphora between conjuncts, despite challenges posed by von Fintel and Iatridou (2017). The key to addressing these challenges is a dynamic, non-modal analysis of imperatives building on Starr (to appear). The other IaDs are explained by appeal to a semantically related use of and, e.g. ‘left-subordinating and (LSand)’ (Culicover and Jackendoff 1997). These other IaDs neutralize the directive meaning of the imperative, and this paper offers a new account of this building on ‘parameter-change conjunction’ (Klinedinst and Rothschild 2012). New data is presented that helps distinguish between the varieties of IaD, and it is shown that the proposed analysis captures it.